Antibody levels against rabies among occupationally exposed individuals in a Nigerian University (2010)
The authors investigated the levels of antiglycoprotein antibodies against rabies virus in the sera of occupationally exposed humans at the University of Ibadan, Nigeria. A quantitative indirect enzyme‐linked immunosorbent assay (ELISA) was used to detect rabies virus anti‐glycoprotein antibodies in sera from 20 zoological garden workers, 20 veterinarians and 30 clinical veterinary students at the University of Ibadan. The sera were obtained between September 2008 and February 2009. Of these 70 healthy individuals, 29 (41.4%) consisting of 15 zoological garden workers (75.0%), 13 veterinarians (65.0%) and 1 veterinary student (3.3%) were immune to rabies virus (antibody titre >0.5 equivalent units per ml), while 41 (58.6%) were not immune. The prevalence of rabies anti‐glycoprotein antibody was higher within the older segment of the study population than among the younger veterinary students. Almost all those who had spent at least 10 years on the job had higher levels of rabies vaccination compliance and were immune. Our results indicated that there is low anti‐rabies immunity among occupationally exposed individuals at the University of Ibadan. There is a need for a complete course of primary and booster vaccinations of professionals exposed to the rabies virus. The impact of these results on rabies control in Nigeria is discussed.